2016
DOI: 10.1063/1.4938239
|View full text |Cite
|
Sign up to set email alerts
|

Tumbling of asymmetric microrods in a microchannel flow

Abstract: We describe results of measurements of the orientational motion of glass microrods in a microchannel flow, following the orientational motion of particles with different shapes. We determine how the orientational dynamics depends on the shape of the particle and on its initial orientation. We find that the dynamics depends so sensitively on the degree to which particle axisymmetry is broken that it is difficult to find particles that are sufficiently axisymmetric so that they exhibit periodic tumbling ("Jeffer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…C om parison w ith Eq. (7) shows that the contribution from convective fluid inertia is of the same order. For nearly spherical particles, by contrast, w e find that convective inertia dom inates (order e), w hile the contribution from unsteady fluid inertia is sm aller, o f order e2.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…C om parison w ith Eq. (7) shows that the contribution from convective fluid inertia is of the same order. For nearly spherical particles, by contrast, w e find that convective inertia dom inates (order e), w hile the contribution from unsteady fluid inertia is sm aller, o f order e2.…”
mentioning
confidence: 89%
“…It is known that the rotation of small particles in a simple shear depends very sensitively on their shape [5][6][7]. Third, for larger particles inertial effects must become important.…”
mentioning
confidence: 98%
“…The particle spin is however hard to measure experimentally, and it is often not analysed. Exceptions are, first, some papers that analyse the angular dynamics of triaxial particles in a simple shear [16][17][18], using Jeffery's theory which also applies to ellipsoids in its general form. Second, Voth et al [19] measured the dynamics of small crosses in turbulence and showed that they tumble like spheroids.…”
Section: Introductionmentioning
confidence: 99%
“…Saffman's lift force and Basset force are also neglected because they are generally much less than the drag force. ( 21) The force and torque exerted on a Fe 3 O 4 aggregate, which is simplified as an ellipsoid with a half-major axis of a and a minor axis of b, are shown in Fig. 2.…”
Section: Principle Of Softening Stoolmentioning
confidence: 99%
“…Under the action of a combination of a fluid field and a magnetic field, the forces applied to magnetic aggregates include contributions from drag force, magnetism, buoyancy force, gravitational force, Brownian force, thermophoretic force, Saffman's lift force, and Basset force. (21) Since only forces in the horizontal plane should be considered, buoyancy force and gravitational force in the vertical direction are neglected. Brownian force can be negligible since Brownian motion is not obvious for these aggregates.…”
Section: Principle Of Softening Stoolmentioning
confidence: 99%